1986
DOI: 10.1113/expphysiol.1986.sp002969
|View full text |Cite
|
Sign up to set email alerts
|

Maternal Heart Rate and Stroke Volume in the Pygmy Goat: Effects of Exercise and Cardiac Autonomic Blockade

Abstract: SUMMARYTo determine the normal maternal heart rate and stroke volume response to exercise and the role of the autonomic nervous system in this response, pregnant and non-pregnant pygmy goats were studied at rest, during and following treadmill exercise, and after autonomic blockade. Resting heart rates, stroke volumes and cardiac outputs were 10%, 60%, and 76% higher in pregnant compared to non-pregnant animals (P < 0 05, 0 001, and 0 001 respectively). During exercise, heart rate and stroke volume rose in bot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

1987
1987
2018
2018

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 17 publications
0
6
0
Order By: Relevance
“…Additionally, stroke volume in pregnant women fell to control values within 3 minutes of recovery whereas it remained above control values at 5 minutes after exercise in postpartum subjects. This fall in stroke volume immediately after exercise also has been observed in pregnant goats, but not in nonpregnant goats 7 . The authors hypothesized that decreased stroke volume after exercise was due to a reduction in preload resulting from decreased venous return in pregnant subjects.…”
Section: Maternal Response To Exercisementioning
confidence: 87%
See 3 more Smart Citations
“…Additionally, stroke volume in pregnant women fell to control values within 3 minutes of recovery whereas it remained above control values at 5 minutes after exercise in postpartum subjects. This fall in stroke volume immediately after exercise also has been observed in pregnant goats, but not in nonpregnant goats 7 . The authors hypothesized that decreased stroke volume after exercise was due to a reduction in preload resulting from decreased venous return in pregnant subjects.…”
Section: Maternal Response To Exercisementioning
confidence: 87%
“…Cardiac output is a function of stroke volume and heart rate, and is increased by 30 to 50% during pregnancy 21 . Several investigators have reported that cardiac output increases further during exercise in pregnant animals 5,7 and humans, 13,15,19 and these values are higher throughout gestation than those of nonpregnant controls 19,22 . In contrast, other investigators have reported similar cardiac outputs in pre‐ and post‐partum subjects after short‐term cycle exercise 14,15 .…”
Section: Maternal Response To Exercisementioning
confidence: 99%
See 2 more Smart Citations
“…Similar results have been reported earlier in goats ( Hoversland et al . 1974 , Hosenpud et al . 1986 , Olsson et al .…”
Section: Discussionmentioning
confidence: 99%